2011
DOI: 10.1007/s13580-011-0168-7
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and histological changes in the fruit abscission zone of water dropwort (Oenanthe stolonifera DC.)

Abstract: Our goal was to investigate fruit abscission in Oenanthe stolonifera DC. by studying the morphological and cytological changes in the abscission zone. One abscission zone existed at the junction between the fruit and the pedicel. The region was clearly distinguishable 10 days after anthesis onwards and consisted of 3 to 5 layers of cells that formed a small, closely packed shape. Cells in the abscission layer began to flatten as the fruit developed. At the beginning of cell separation, cells in the middle area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The protein products of these molecules are probably essential for cell wall hydrolysis and modifications, e.g., cellulases, polygalacturonases, and may directly influence the middle lamella dissolution followed by cell wall rapture, as was confirmed in other plant species (Bonghi et al 1992; Kalaitzis et al 1997; Belfield et al 2005; Ogawa et al 2009). The evidence supporting the thesis concerning de novo protein synthesis during separation event initiation was provided on the basis of studies conducted in Oenanthe stolonifera (Eo and Lee 2011). Similar cytosol localization pattern of LlBOP and poly(A) mRNA (Figs.…”
Section: Discussionmentioning
confidence: 91%
“…The protein products of these molecules are probably essential for cell wall hydrolysis and modifications, e.g., cellulases, polygalacturonases, and may directly influence the middle lamella dissolution followed by cell wall rapture, as was confirmed in other plant species (Bonghi et al 1992; Kalaitzis et al 1997; Belfield et al 2005; Ogawa et al 2009). The evidence supporting the thesis concerning de novo protein synthesis during separation event initiation was provided on the basis of studies conducted in Oenanthe stolonifera (Eo and Lee 2011). Similar cytosol localization pattern of LlBOP and poly(A) mRNA (Figs.…”
Section: Discussionmentioning
confidence: 91%
“…We showed that cells of the AZ isolated from naturally abscised flowers divided intensively and were linked by numerous plasmodesmata, which suggest the possibility of intercellular communication [29]. The cytoplasm of active AZ cells was dense, heterogeneous, and enriched in proteins, suggesting the de novo synthesis of enzymes crucial for organ separation [30]. Analyses performed using transmission electron microscopy also revealed that these cells were progressively degraded.…”
Section: Introductionmentioning
confidence: 87%
“…This, in turn, triggers in the cytoplasm of AZ cells a signal transduction pathway involving MAP kinases that activates transcriptional factors, e.g., KNAT2 and KNAT6 (knotted-like from Arabidopsis thaliana 2 and 6), which induce organ abscission [ 23 , 24 ]. AZ activation requires intensive de novo synthesis of proteins [ 25 ] that are involved in the degradation of cell walls, but also in some cases the formation of newly-formed cell walls of daughter cells. Moreover, observations of cell organelles, including chloroplasts and nuclei, indicated DNA fragmentation and possible induction of programmed cell death (PCD), probably caused by intensive reactive oxygen species (ROS) generation [ 2 , 20 , 23 , 24 , 26 ].…”
Section: Introductionmentioning
confidence: 99%